Susceptibility of Chikungunya Virus to Inactivation by Heat and Commercially and World Health Organization-Recommended Biocides. (15th June 2018) - Franz, Sergej; Friesland, Martina; Passos, Vânia; Todt, Daniel; Simmons, Graham; Goffinet, Christine; Steinmann, Eike
Abstract: Despite increasing clinical relevance of Chikungunya virus (CHIKV) infection, caused by a rapidly emerging pathogen, recommended guidelines for its inactivation do not exist. In this study, we investigated the susceptibility of CHIKV to inactivation by heat and commercially available hand, surface, and World Health Organization-recommended disinfectants to define CHIKV prevention protocols for healthcare systems. Abstract : In this study, we characterized the stability of Chikungunya virus to heat inactivation and susceptibility to various commercially available hand- and surface- as well as WHO-recommended disinfectants to aid the development of appropriate disinfection and sanitization regimens.